Morning Connections: How do you support hospital staff working remotely during a global pandemic without providing 'staff support'?. (January 2023) - Flannery, Halina; McParland, James; Baker, Hannah; Hitchcock, Megan; Portnoy, Sara
When lockdown was announced in the United Kingdom, kitchen tables transformed into offices overnight, as many National Health Service (NHS) workers adapted to new ways of working from home. To respond to the developing situation, we established a programme of weekly 'Connections' meetings where staff could be together, remotely. This article describes the evolution of our Morning Connections and Oncology Connections virtual meetings, including the content of sessions, how they were evaluated and whether they met their intention to support colleagues during a particularly challenging time, both personally and professionally, for NHS staff.